SEJARAH PENDIDIKAN ISLAM DI MINANGKABAU - Saharman Saharman (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to describe the development of Islamic education in Minangkabau. Library studies are used in collecting data and analyzing data qualitatively. The development of Islamic Education Institutions in the archipelago shows the influence of the development of Islamic education in the Middle East, especially Mecca and Cairo, although in detail there are differences in understanding. This influence was brought by natives who were initially to perform the pilgrimage, but then most of them settled there a few years to seek knowledge. Not much different from Minangkabau, at the end of the 17th century, it was influenced by Aceh by Syekh Burhanuddin Ulakan who went to study religious knowledge for several years, and then after returning home, established a mosque in the form of an educational institution with a halakah system. Furthermore, in the 20th century the madrasa was established as a sign of the beginning of the renewal of Islamic education by the best sons of Minangkabau by following the system carried out by previous ulama scholars, so that Islamic Education Institutions in Minangkabau continued to develop into universities. It is concluded that Syeh Burhanuddin has influence in the history of the development of Islamic education in Minangkabau.